Quininium tetrachloridozinc(II) - Li-Zhuang Chen (Acta Crystallographica Section E, 2009)
The asymmetric unit of the title compound {systematic name: 2-[hydroxy(6-methoxyquinolin-1-ium-4-yl)methyl]-8-vinylquinuclidin-1-ium tetrachloridozinc(II)}, (C20H26N2O2)[ZnCl4], consists of a double protonated quininium cation and a tetrachloridozinc(II) anion. The ZnII ion is in a slightly distorted tetrahedral coordination environment. The crystal structure is stabilized by intermolecular N—H...Cl and O—H...Cl hydrogen bonds.